Finite element reduction strategy for composite sandwich plates with viscoelastic layers - Diacenco,Adriana Amaro (2013)
Composite materials have been regarded as a convenient strategy in various types of engineering systems such as aeronautical and space structures, as well as architecture and light industry products due to their advantages over the traditional engineering materials, such as their high strength/stiffness relation characteristics and their anti-corrosion properties. This paper is devoted to the finite element modeling of composite laminated structures incorporating viscoelastic materials to the problem of vibration attenuation. However, the typically high dimension of large finite element models of composite structures incorporating viscoelastic materials makes the numerical processes sometimes unfeasible. Within this context, emphasis is placed on a general condensation strategy specially adapted for the case of viscoelastically damped structures, in which a constant (frequency- and temperature-independent) reduction basis to be enriched by static residues associated to the applied loads and the viscoelastic forces is used. After presenting the theoretical foundations, the numerical applications of composite plates treated by viscoelastic materials are addressed, and the main features of the methodology are discussed.